Apakah Fungsi Belanja APBD Dan Dana Desa Mempengaruhi Indeks Pembangun Ekonomi Inklusif di Indonesia? - Pardomuan Robinson Sihombing; Ade Marsinta Arsani; Dyah Purwanti (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2023)
This study aims to examine the effect of the function of Regional Government Budget expenditure and village funds on the Inclusive Economic Development Index (IEDI) in Indonesia. The spending approach uses the income variables of Health Function, Education Function, Social Protection Function and Village Fund. The data is sourced from Bappenas and the Statistics Indonesia for the period 2018-2021. The statistical method used is multiple linear regression with panel data. Based on panel model testing, Fixed model is the best model. Simultaneously all variables affect IPEI. Partially, the Health Function, Education Function, Social Protection Function and Village Fund have a significant positive effect on IEDI. Based on the results of this study, a comprehensive policy related to macro-social economy is needed so that Indonesia's IEDI level continues to increase.